Occupational therapy for people with dementia and their family carers provided at home: a systematic review and meta-analysis. Issue 11 (11th November 2019) - Bennett, Sally; Laver, Kate; Voigt-Radloff, Sebastian; Letts, Lori; Clemson, Lindy; Graff, Maud; Wiseman, Jodie; Gitlin, Laura
Abstract : Objective: To determine the effect of occupational therapy provided at home on activities of daily living, behavioural and psychological symptoms of dementia (BPSD) and quality of life (QOL) for people with dementia, and the effect on family carer burden, depression and QOL. Design: Systematic review and meta-analysis. Methods: Eight databases were searched to February 2018. Randomised controlled trials of occupational therapy delivered at home for people with dementia and their family carers that measured ADL, and/or BPSD were included. Two independent reviewers determined eligibility, risk of bias and extracted data. Results: Fifteen trials were included (n=2063). Occupational therapy comprised multiple components (median=8 sessions). Compared with usual care or attention control occupational therapy resulted in improvements in the following outcomes for people with dementia: overall ADL after intervention (standardised means difference (SMD) 0.61, 95% CI 0.16 to 1.05); instrumental ADL alone (SMD 0.22, 95% CI 0.07 to 0.37; moderate quality); number of behavioural and psychological symptoms (SMD −0.32, 95% CI −0.57 to −0.08; moderate quality); and QOL (SMD 0.76, 95% CI 0.28 to 1.24) after the intervention and at follow-up (SMD 1.07, 95% CI 0.58 to 1.55). Carers reported less hours assisting the person with dementia (SMD −0.33, 95% CI −0.58 to −0.07); had less distress with behaviours (SMD −0.23, 95% CI −0.42 to −0.05; moderate quality) and improved QOL (SMD 0.99, 95% CI 0.66 to 1.33; moderate quality). Two studies compared occupational therapy with a comparison intervention and found no statistically significant results. GRADE ratings indicated evidence was very low to moderate quality. Conclusions: Findings suggest that occupational therapy provided at home may improve a range of important outcomes for people with dementia and their family carers. Health professionals could consider referring them for occupational therapy. PROSPERO registration number: CRD42011001166.